Liquid crystal monomers induce placental development and progesterone release dysregulation through transplacental transportation - Shaohan Zhang; Zhipeng Cheng; Tao Zhang; Yubin Ding; Hongkai Zhu; Lei Wang; Hongwen Sun (Nature Communications)
Abstract Embryonic and fetal development can be affected during gestation by exposure to xenobiotics that cross the placenta. Liquid crystal monomers (LCMs) are emerging contaminants commonly found in indoor environments; however, whether they can cross the placenta and affect placental development remains unexplored. Here, we develop an evaluation system that integrates human biomonitoring, uterine perfusion in pregnant rats, and placental cells. We find fourteen out of the fifty-six LCMs that are detected in maternal and cord serum samples from ninety-three healthy pregnant women, at median levels of 13.9 and 18.1 ng/mL, respectively. Subsequent explorations of in utero exposure in rats indicate that aromatic amino acid transporter 1 (SLC16A10) mediates transplacental transportation of the LCMs. Placental cells exposed to LCMs exhibit delayed placental development and reduced progesterone release. These findings show that SLC16A10-mediated transplacental transportation of LCMs inhibits placental development and progesterone release, highlighting the importance of gestational exposure to emerging contaminants.